Improvement of organizational and technological solutions considering energy efficiency principles and sustainable development in civil construction - PASTUKHOVA, Susanna; ARUTIUNIAN, Iryna; AZHAZHA, Maryna (Ways to Improve Construction Efficiency, 2025)
The article thoroughly considers the key role of modern technological solutions in meeting the urgent need to improve the energy efficiency of buildings in the context of sustainable development. A number of innovative approaches and the latest technological achievements focused on reducing energy consumption, optimizing the operational characteristics of buildings and minimizing the negative impact on the environment are analyzed in detail. Theoretical and applied aspects of improving organizational and technological solutions in civil engineering from the standpoint of rational use of energy resources, optimization of processes of providing material and technical means, time and labor resources management are considered. Particular attention is paid to the creation of mathematical models that allow taking into account a complex of interrelated parameters – energy consumption, technological sequence, environmental constraints, economic efficiency. Approaches to the integration of models into the processes of design and implementation of construction projects are proposed, with an emphasis on increasing the predictability of results and making informed management decisions. The results of the study are of practical value for construction organizations, design institutions, scientific institutions, as they make it possible to implement innovative organizational and technological solutions taking into account the requirements of sustainable development. The developed approach can be used to increase the efficiency of construction management at all stages of the object life cycle, contributing to increasing the competitiveness of the industry in the context of global transformations. As a result, the decisive importance of scientific and technological progress and innovation in achieving energy goals, as well as the need for an interdisciplinary approach to the introduction of energy efficient technologies, is emphasized.